Nihon gakki hō CD tsuki - Miki, Minoru (Ongaku no Tomosha, 1996)
Introduction to traditional Japanese musical instruments such as koto, shakuhachi, shamisen, and taiko, with photographs and samples of musical notations. Two CDs accompany the text so that users can hear samples of both the instruments and the different playing styles, performed by the Nihon Ongaku Shūdan
Keywords: Musik; Musical instruments / Japan; Music / Japan